THE EFFECT OF EXPERIENCE, SKILL AND ENVIRONMENT ON DECISION MAKING (LITERATURE REVIEW STUDY) - Hermawan, Eric (Dinasti Publisher, 2022)
Literature review article on the influence of experience, skills and the environment on decision making is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Experience influences Decision Making; 2) Skill has an effect on Decision Making; and 3) Environment influences Decision Making. Apart from these 3 exogenous variables that affect the endogenous variables of Decision Making, there are still many other factors including the variables of Leadership, Motivation, Education.